2021
DOI: 10.1136/bmjopen-2020-044797
|View full text |Cite
|
Sign up to set email alerts
|

Developing a core outcome set for traumatic brachial plexus injuries: a systematic review of outcomes

Abstract: ObjectiveTo identify what outcomes have been assessed in traumatic brachial plexus injury (TBPI) research to inform the development of a core outcome set for TBPI.DesignSystematic review.MethodMedline (OVID), EMBASE, CINAHL and AMED were systematically searched for studies evaluating the clinical effectiveness of interventions in adult TBPIs from January 2013 to September 2018 updated in May 2021. Two authors independently screened papers. Outcome reporting bias was assessed. All outcomes were extracted verbat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…The findings from our consensus process highlighted differences between the outcomes reported in current TBPI studies and those prioritized as important by HCP and patient stakeholder groups. Strength is measured and reported in approximately 90% of studies including patients with a TBPI ( Dy et al., 2015 ; Miller et al., 2021 ). However, strength as a single domain was not prioritized by the stakeholders in our study.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The findings from our consensus process highlighted differences between the outcomes reported in current TBPI studies and those prioritized as important by HCP and patient stakeholder groups. Strength is measured and reported in approximately 90% of studies including patients with a TBPI ( Dy et al., 2015 ; Miller et al., 2021 ). However, strength as a single domain was not prioritized by the stakeholders in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The longlist of outcomes was generated from two sources: first, through a systematic review of outcomes reported in studies evaluating interventions for individuals with a TBPI ( Miller et al., 2021 ); and second, through patient interviews to identify outcomes important to adults with a TBPI (Miller et al., 2022). The outcomes extracted from the systematic review and identified from the interviews were grouped into domains and categorized into a taxonomy developed to support COS generation ( Dodd et al., 2018 ) by the lead author (CM) and reviewed by the co-authors.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Successful outcomes are commonly associated with objective measurements of muscle strength; with the Medical Research Council (MRC) grade and muscle dynamometry being the most frequently reported. 1,2 Typically, these studies examine isolated muscle strength, with the upper arm supported in a standardised position. When put in the context of everyday life, this information is not transferable to activities of daily living and does not consider the deficits in function that a loss of movement and sensation may contribute to.…”
Section: Introductionmentioning
confidence: 99%